2019
DOI: 10.1080/03601234.2019.1604039
|View full text |Cite
|
Sign up to set email alerts
|

Development of enterosorbents that can be added to food and water to reduce toxin exposures during disasters

Abstract: Humans and animals can be exposed to mixtures of chemicals from food and water, especially during disasters such as extended droughts, hurricanes and floods. Drought stress facilitates the occurrence of mycotoxins such as aflatoxins B1 (AfB1) and zearalenone (ZEN), while hurricanes and floods can mobilize toxic soil and sediments containing important pesticides (such as glyphosate). To address this problem in food, feed and water, we developed broad-acting, clay-based enterosorbents that can reduce toxin expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…To develop broad-acting sorbents that can reduce exposures to diverse mixtures of environmental chemicals, we have treated montmorillonites with acid to increase their surface area and porosity, resulting in more active sites for toxin sequestration and binding. The safety of broad-acting APMs and their increased efficacy for aflatoxins, zearalenone, glyphosate, and PCBs have been previously described [24,25]. This study was designed to investigate the binding efficacy of APMs for widely used and highly toxic pesticides (individuals and mixtures) with different structural morphologies and modes of toxic action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To develop broad-acting sorbents that can reduce exposures to diverse mixtures of environmental chemicals, we have treated montmorillonites with acid to increase their surface area and porosity, resulting in more active sites for toxin sequestration and binding. The safety of broad-acting APMs and their increased efficacy for aflatoxins, zearalenone, glyphosate, and PCBs have been previously described [24,25]. This study was designed to investigate the binding efficacy of APMs for widely used and highly toxic pesticides (individuals and mixtures) with different structural morphologies and modes of toxic action.…”
Section: Discussionmentioning
confidence: 99%
“…To develop broad-acting sorbents to mitigate pesticide exposures and toxicities, we have treated both calcium and sodium montmorillonite clays (CM and SM) with 12 and 18 normality sulfuric acid to produce high surface area and enhanced porosity. These acid-processed calcium and sodium montmorillonites (APCMs and APSMs) have been previously reported to bind hazardous mixtures of mycotoxins (aflatoxin and zearalenone), a commonly occurring herbicide (glyphosate) and polychlorinated biphenyls (PCBs) [ 24 , 25 ]. Based on earlier work with acid processed montmorillonite clays (APMs), we have postulated that treatment of clays with high concentrations of acid results in the exchange of interlayer cations with protons from the acid, followed by the dissolution of portions of the octahedral and tetrahedral framework in the clay structure [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…To establish the dose and time dependences of response to toxins alone, experiments were first conducted with glyphosate (0, 10, 30, 40, and 60 ppm) and paraquat (0, 5, 10, 20, and 30 ppm), with hydra morphological response scored and recorded at 0, 4, 20, 28, 44, 68, and 92 h. 74,75 The concentration ( C )–time ( t )–response ( y ) relationship was fit to both a power-exponential and a Hill modelThe responses at C = 0 and t = 0 time were constrained to be 10, because all untreated hydra were uniformly unaffected. Model fitting was conducted using nonlinear least squares (nls function in the R statistical software, version 3.4.2); model fits were compared using the AIC, and confidence intervals were calculated based on Monte Carlo estimates from the R package propagate.…”
Section: Methodsmentioning
confidence: 99%
“…Materials such as activated carbon (AC) and clay-based sorbents have been used to bind various contaminants in the environment to reduce their bioavailability. Studies from our laboratory have shown that montmorillonite-based clays are highly effective sorbents for mycotoxins, pesticides, PAHs, and PCBs (Hearon et al, 2020;Phillips et al, 2019;Wang et al, 2019a, Wang et al, 2019bWang et al, 2020). We have recently shown that calcium montmorillonite (CM) clay can tightly bind PMG to active surfaces based on adsorption studies and computational modeling (Wang et al, 2019c).…”
Section: Introductionmentioning
confidence: 99%